Cotton Solitons on Three Dimensional Almost $ - Erken, İrem Küpeli; Özkan, Mustafa; Savur, Büşra (Kazım İLARSLAN, 2023)
In this paper, we study Cotton solitons on three-dimensional almost ?-paracosymplectic manifolds. We especially focus on threedimensional almost ?-paracosymplectic manifolds with harmonic vector field ? and characterize them for all possible types of operator h. Finally, we constructed an example which satisfies our results.
alpha$-paracosymplectic Manifolds
Keywords: Algebraic and Differential Geometry; Cebirsel ve Diferansiyel Geometri